The Influence of Public Ownership, Listing Age, and Number of Independent Commissioners on the Timeliness of Corporate Internet Reporting in Property and Real Estate Companies on the Indonesia Stock Exchange for the 2021-2023 Period - Batubara, Faisal H.; Hasanah; Mulatsih (Global Writing Academica Researching & Publishing, 2024)
This study aims to examine whether or not there is an influence between public ownership, listing age, and total independent board of commissioners on the timeliness of Corporate Internet Reporting in property and Real Estate companies on the IDX during the 2021-2023 period. The method for this research is quantitative, and the data source obtained for this research is secondary data. The sample collection technique used in this study is the criteria selection method or commonly refrred to as purposive sampling. The procedures in the data analysis technique in this study include logistic regression analysis and descriptive statistics. The conclusion obtained from the result of the analysisis that public ownership, listing age, and total number of independent commissioners have an influence on the timeliness of CIR in property and real estate companies on the IDX during the period 2021-2023.